Ground Water and Vadose Zone Monitoring 1990
DOI: 10.1520/stp23404s
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Conductivity Determinations in Unlithified Glacial and Fluvial Materials

Abstract: Experiences with many measurements of the hydraulic conductivity of unlithified glacial and fluvial materials in Wisconsin suggest that hydraulic conductivity must be viewed in terms of the operational scale of measurement, based on the scale of the problem at hand and the volume of the materials of interest. Frequently, the hydraulic conductivity of a given lithostratigraphic unit appears to increase as the operational scale of measurement increases. In particular, laboratory methods can yield hydraulic condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 11 publications
4
52
0
Order By: Relevance
“…Previous studies have also shown that K s increases as the scale of measurement or sampling volume increases particularly for structured soils with macroporosity (e.g. Bagarello, 1997;Bradbury and Muldoon, 1990). Therefore, small sample volumes may fail to account for K s arising from macropore or preferential flow (Mallants et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that K s increases as the scale of measurement or sampling volume increases particularly for structured soils with macroporosity (e.g. Bagarello, 1997;Bradbury and Muldoon, 1990). Therefore, small sample volumes may fail to account for K s arising from macropore or preferential flow (Mallants et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are problems applying a single equation to sediments from a naturally heterogeneous environment (Bradbury and Muldoon, 1990), the Hazen formula has been shown to produce less variable results than some other methods derived from sandy substrates (Goodman, 1999) and has been used previously in studies of glaciofluvial deposits (e.g. Anderson et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Bradbury and Muldoon (1990) and Rehfeldt et al (1992) reported differences of one-to two-orders of magnitude, and Wolf et al (1991) and Rovey and Niemann (2001) reported differences of one-order of magnitude. These differences result, in part, from the volume of aquifer influenced during the test and how the heterogeneities encountered within this volume are spatially averaged by the test (e.g., Desbarats, 1994;Sánchez-Vila et al, 1996;Rovey and Niemann, 2001;Beckie and Harvey, 2002;Molz et al, 2005).…”
Section: Figure 1-5mentioning
confidence: 98%
“…These differences result, in part, from the volume of aquifer influenced during the test and how the heterogeneities encountered within this volume are spatially averaged by the test (e.g., Desbarats, 1994;Sánchez-Vila et al, 1996;Rovey and Niemann, 2001;Beckie and Harvey, 2002;Molz et al, 2005). To investigate the dependency of our measured hydraulic conductivities on the measurement scale, we chose the test volume as a measure of scale (Bradbury and Muldoon, 1990;SchulzeMakush et al, 1999 Methods that are more rigorous for estimating support volumes for pumping and slug tests have been developed for specific flow conditions (e.g., Desbarats, 1994;Beckie, 2001;Beckie and Harvey, 2002;Molz et al, 2005). However, applying these methods to the test conditions present at our site is outside of the scope of this research.…”
Section: Figure 1-5mentioning
confidence: 99%